Developing 'Smart' Solutions for Light Management for Historic Collections. (31st August 2020) - Vlachou-Mogire, Constantina; Bertolotti, Giulia; Hallett, Kathryn; Frame, Kate
ABSTRACT: In 2011 Historic Royal Palaces began to investigate protective measures for historic tapestries on open display at Hampton Court Palace. The environmental exposure conditions for each tapestry were analysed and mapped to evaluate risk. An innovative method to reduce illuminance and direct sunlight on the historic tapestries using 'smart' technologies was developed. The design, testing and implementation of the installation of Smart Tint liquid crystal films whose optical appearance can be switched electrically from opaque to transparent, are presented. Substantial reduction (>90%) in direct light transmission could be achieved when the film is opaque. It also provides additional protection from ultraviolet (99%) and infrared radiation (98%). An entirely reversible and customised installation method had to be devised using pressure-fixed lightweight aluminium frames. An automated controller was also installed to change the individual windows from clear to opaque during different times of the day depending on their orientation and the time of the year while a dedicated wireless mesh network system enabled communication between each window and the controller. The impact of this installation is described. The use of 'smart' technologies offered dynamic light protection for collections on open display while maintaining the presentation of the historic room. The benefits of adopting this innovative technology include its flexible and unobtrusive installation.